PENGARUH KUALITAS PRODUK, PERSEPSI HARGA DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN DI KOPI KENANGAN KOTA KASABLANKA - Jonathan Caesar Putra; Ricky Talumantak (GoAcademica Research dan Publishing, 2022)
The study aims to determine and Product Quality, Price Perception and Brand Image on Purchase Decisions at Kopi Kenangan Kota Kasablanka. The data used is primary data by collecting questionnaire data by processing data using the SPSS Version 21 application to obtain the research population is all consumers who come to Kopi Kenangan Kota Kasablanka. Samples were taken as many as 100 respondents using the Accidental Sampling technique. In this study also used multiple linear regression analysis. The technique used to calculate the data is the classical assumption test such as the data normality test, heteroscedasticity test, and multicollinearity test. There is also a data hypothesis using the F-test and T-test calculations. So, the results of this study partially state that the product quality and brand image variables have no significant effect on purchasing decisions, while the price perception variable has a significant positive effect on purchasing decisions. Simultaneously product quality, price perception and brand image affect purchasing decision.